(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Katarina Popović Midžina’s Great Serbian Cookbook, with its six editions from 1876 to World War II, is an indispensable source of information when it comes to the alimentation habits of the urban population in the second half of the 19th and the early 20 th century. This cookbook, however, does not describe Serbian traditional cuisine, but presents to the Serbian audience a selection of dishes from developed European cuisines, primarily the Viennese cuisine. In this light, this cookbook presents an effort to name and describe in the Serbian language foods and dishes that until then were not part of the Serbian food tradition, and therefore were not named. Although often cited according to different editions, this work has not been the subject of detailed analysis. In particular, there are serious differences between the third and fourth edition, mainly due to the efforts of Mileva Simić, whose authorial role has remained completely hidden. In order to examine her role in the reshaping of the Great Serbian Cookbook, a digital corpus consisting of the text of the third edition, which contains the unchanged second edition, and the fourth edition was compiled. This corpus illustrates the language of Midžina (second edition), anonymous users of the book (appendix to the third edition) and Mileva Simić (fourth edition). Starting from the results of processing the corpus, the effort of both authors to develop the necessary terminological apparatus in the Serbian language for describing culinary procedures and products is recognized, which is reflected in “artificial expressions”, as Midžina calls them. These terms (for foods or dishes) are Serbian coined expressions for foreign, primarily German, culinary terms. As the corpus shows, the terms coined in this way did not always have a clear meaning and a precise relationship to the foreign equivalent, and they were not in accordance with the already accepted loanwords, as evidenced, above all, by the corpus of literary works from the same era. Starting from Midžina’s idea, Mileva Simić adapted the text of the recipes to the tastes of the users at her time, omitting unusual ingredients. Also, terminologically, she separated numerous culinary concepts that Midžina did not discern. The paper shows the evolution of the texts of these cookbooks and analyses examples that show their differences in the authors’ naming of ingredients and dishes, as well as the relationship to later accepted terminological solutions, primarily in the cookbook by Spasenija Marković, known as Pata’s Cookbook.